Adipokines: New Potential Therapeutic Target for Obesity and Metabolic, Rheumatic, and Cardiovascular Diseases - Recinella, Lucia; Orlando, Giustino; Ferrante, Claudio; Chiavaroli, Annalisa; Brunetti, Luigi; Leone, Sheila (Frontiers in Physiology, 2020)
Besides its role as an energy storage organ, adipose tissue can be viewed as a dynamic and complex endocrine organ, which produces and secretes several adipokines, including hormones, cytokines, extracellular matrix (ECM) proteins, and growth and vasoactive factors. A wide body of evidence showed that adipokines play a critical role in various biological and physiological functions, among which feeding modulation, inflammatory and immune function, glucose and lipid metabolism, and blood pressure control. The aim of this review is to summarize the effects of several adipokines, including leptin, diponectin, resistin, chemerin, lipocalin-2 (LCN2), vaspin, omentin, follistatin-like 1 (FSTL1), secreted protein acidic and rich in cysteine (SPARC), secreted frizzled-related protein 5 (SFRP5), C1q/TNF-related proteins (CTRPs), family with sequence similarity to 19 member A5 (FAM19A5), wingless-type inducible signaling pathway protein-1 (WISP1), progranulin (PGRN), nesfatin-1 (nesfatin), visfatin/PBEF/NAMPT, apelin, retinol binding protein 4 (RPB4), and plasminogen activator inhibitor-1 (PAI-1) in the regulation of insulin resistance and vascular function, as well as many aspects of inflammation and immunity and their potential role in managing obesity-associated diseases, including metabolic, osteoarticular, and cardiovascular diseases.